State‐of‐the‐art in marketed adjuvants and formulations in Allergen Immunotherapy: A position paper of the European Academy of Allergy and Clinical Immunology (EAACI). Issue 4 (21st April 2020) - Jensen‐Jarolim, Erika; Bachmann, Martin F.; Bonini, Sergio; Jacobsen, Lars; Jutel, Marek; Klimek, Ludger; Mahler, Vera; Mösges, Ralph; Moingeon, Philippe; O´Hehir, Robyn E.; Palomares, Oscar; Pfaar, Oliver; et al.
Abstract: Since the introduction of allergen immunotherapy (AIT) over 100 years ago, focus has been on standardization of allergen extracts, with reliable molecular composition of allergens receiving the highest attention. While adjuvants play a major role in European AIT, they have been less well studied. In this Position Paper, we summarize current unmet needs of adjuvants in AIT citing current evidence. Four adjuvants are used in products marketed in Europe: aluminium hydroxide (Al(OH)3 ) is the most frequently used adjuvant, with microcrystalline tyrosine (MCT), monophosphoryl lipid A (MPLA) and calcium phosphate (CaP) used less frequently. Recent studies on humans, and using mouse models, have characterized in part the mechanisms of action of adjuvants on pre‐existing immune responses. AIT differs from prophylactic vaccines that provoke immunity to infectious agents, as in allergy the patient is presensitized to the antigen. The intended mode of action of adjuvants is to simultaneously enhance the immunogenicity of the allergen, while precipitating the allergen at the injection site to reduce the risk of anaphylaxis. Contrasting immune effects are seen with different adjuvants. Aluminium hydroxide initially boosts Th2 responses, while the other adjuvants utilized in AIT redirect the Th2 immune response towards Th1 immunity. After varying lengths of time, each of the adjuvants supports tolerance. Further studies of the mechanisms of action of adjuvants may advise shorter treatment periods than the current three‐to‐five‐year regimens, enhancing patient adherence. Improved lead compounds from the adjuvant pipeline are under development and are explored for their capacity to fill this unmet need. Abstract :